Catalyst-controlled directing group translocation in the site selective C–H functionalization of 3-carboxamide indoles and metallocarbenes - Kuang Gu; Mary T. Hall; Zachary D. Tucker; Gregory M. Durling; Brandon L. Ashfeld (Nature Communications)
Abstract Complementary methods toward the selective functionalization of indole and oxindole frameworks employing an alternative strategy in heteroaryl C–H functionalizations are presented herein. This work focuses on a catalyst-controlled, site selective C–H activation/functionalization of 3-acyl indoles, wherein an amide serves as a robust and versatile directing group capable of undergoing concomitant 1,2-acyl translocation/C–H functionalization in the presence of a RhI/AgI co-catalysts to provide the cross-coupled adducts in high yields. In contrast, the use of IrIII/AgI catalysts subverted the 1,2-acyl migration to afford the corresponding C2-functionalized products in good to excellent yields. A notable feature of the catalyst systems was the exceptional level of site selectivity observed in which the corresponding C–H functionalized indoles were obtained exclusively. Mechanistic experiments indicate a concerted 1,2-acyl migration step and indole metallation occurring through an electrophilic aromatic substitution process.